Identification of miRNAs Contributing to the Broad-Spectrum and Durable Blast Resistance in the Yunnan Local Rice Germplasm - Li, Jinlu; Zhang, Hui; Yang, Rui; Zeng, Qianchun; Han, Guangyu; Du, Yunlong; Yang, Jing; Yang, Genhua; Luo, Qiong (Frontiers in Plant Science, 2021)
MicroRNAs are 20–24 nucleotide non-coding RNAs and play important roles in plant-environment interactions. In recent years, many microRNAs (miRNAs) have been found to regulate rice immunity against rice blast fungus. However, there are limited studies about miRNAs that directly target resistance (R) genes to regulate rice immunity. In this study, by deep sequencing, small RNA libraries were constructed from four-leaf stage seedlings of the resistant variety Ziyu44 and susceptible variety Jiangnanxiangnuo (JNXN) upon Magnaporthe oryzae infection, we found that much more miRNAs were significantly differentially expressed in Ziyu44 than in JNXN. Among these miRNAs, we focused on miR9664, a newly identified rice miRNA in our sequencing, which was upregulated lightly in Ziyu44 and drastically in JNXN at 24–48 h post-inoculation (hpi). The transgenic plants overexpressing miR9664 (miR9664-oe) displayed reduced defense responses to M. oryzae, while those knocking down miR9664 (miR9664-m) displayed enhanced defense responses to M. oryzae. Most of the detected miR9664 predicted target genes were reduced in the miR9664-oe lines while increased in the miR9664-m lines. The cleavage site of LOC_Os08g07774 was confirmed by RLM-RACE. Meanwhile, after being inoculated with M. oryzae, the genes were expressed differently between Ziyu44 and JNXN. The results suggest that miR9664-mediated R gene turnover contributes to Ziyu44 broad-spectrum resistance to rice blast fungus. Taken together, our research identified a new rice miRNA that directly targets R genes to regulate rice immunity against rice blast fungus, adding significant information to the study of rice–M. oryzae interaction.